Assessing Cashew Orchards Management Practices and Infestation rates of Apate terebrans in Orchards in Burkina Faso, West Africa - SOMDA, Naamwin Irkoum Zephirin; UGWU, Juliana Amaka (Andalasian International Journal of Entomology, 2024)
Cashew is a significant export crop in Burkina Faso but suffers substantial damage from the cashew wood borer Apate terebrans Pallas. Despite its economic importance, the population dynamics of this beetle have not previously been studied in Burkina Faso, limiting the development of effective control strategies. This study monitored infestation patterns on 960 cashew trees randomly selected from 8 localities in 4 regions across two agro-ecological zones. The trees were inspected monthly over two consecutive years according to typical producer management practices. As A. terebrans bores inside branches and trunks, direct observation of adults was unfeasible. Therefore, infestation rates were estimated by counting fresh entry holes monthly. Over the study period, infestations began in July, peaked in November–December, and declined to zero by May–June. Infestation rates differed significantly between years (p < 0.001), among regions (p < 0.001) and localities (p < 0.02), and were influenced by cashew tree phenology (p < 0.01), suggesting that A. terebrans preferentially infests uncleaned orchards and trees at more vulnerable phenological stages. These findings underscore the need for targeted orchard sanitation practices to reduce infestations, as well as the importance of sampling plans and population monitoring to support higher cashew yields and economic returns.